2000
DOI: 10.1016/s0895-7061(99)00169-7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-derived factors in microalbuminuric and nonmicroalbuminuric essential hypertensives

Abstract: Previous evidence has demonstrated a relationship between growth factors and cardiovascular diseases. This study was aimed at evaluating levels of some endothelium-derived growth factors, and their relationship with microalbuminuria (MAU), in essential hypertension. Ninety-nine mild-moderate essential hypertensives (EH) and 25 healthy controls were studied. All patients underwent 24-h blood pressure monitoring, serum endothelin-1 (ET-1), basic fibroblast growth factor (bFGF) and platelet-derived growth factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…VEGF may induce microalbuminuria by afferent glomerular arteriolar vasodilation and enhanced EC permeability. ET-1, FGF-2 and PDGF-AB levels are elevated in hypertensive patients with microalbuminuria compared to hypertensive patients without microalbuminuria and to normotensive controls [93]. Early clinical trials with FGF-2 have also reported proteinuria as a significant side effect [21,94].…”
Section: Potential Clinical Significance Of Elevated Vegf Levels In Hmentioning
confidence: 99%
See 3 more Smart Citations
“…VEGF may induce microalbuminuria by afferent glomerular arteriolar vasodilation and enhanced EC permeability. ET-1, FGF-2 and PDGF-AB levels are elevated in hypertensive patients with microalbuminuria compared to hypertensive patients without microalbuminuria and to normotensive controls [93]. Early clinical trials with FGF-2 have also reported proteinuria as a significant side effect [21,94].…”
Section: Potential Clinical Significance Of Elevated Vegf Levels In Hmentioning
confidence: 99%
“…Levels of insulin growth factor binding protein-1 (IGBP-1) are elevated in hypertension [51]. FGF-2 levels are elevated in mild-moderate hypertension compared with normotensive controls [52]. PDGF-AB levels are not elevated in hypertensive patients compared to controls, except in the subset of hypertensive patients with microalbuminuria [52].…”
Section: Angiogenic Growth Factor Levels In Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 It is also important to discuss in this same context the relationship of microalbuminuria and endothelial function, a parameter frequently abnormal in essential hypertension, that may precede and accelerate atherosclerotic progression. 31 On one hand, consistent evidence does suggest that hypertensive microalbuminuria is associated with circulating markers of endothelial dysfunction, [32][33][34][35] including von Willebrand Factor, an endothelial haemostatic factor and a predictor of cardiovascular death. 36 On the other hand, however, urine albumin was dissociated from both the transcapillary 125 I-albumin escape rate, a measure of systemic capillary permeability, 28,37 and forearm vasodilatation to acetylcholine, 38 a compound that releases nitric-oxide from endothelial cells.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%